From awareness to action: behavioral change is associated with functional gains and injury reduction in elite runners - a prospective observational study - Murofushi, K.; Mitomo, S.; Yamada, Y.; Hirohata, K.; Furuya, H.; Katagiri, H.; Akuzawa, H.; Hara, S.; Ito, M.; Ohmi, T.; Kaneoka, K. (Frontiers in Psychology, 2026)
Background: Running-related injuries (RRIs) are a major concern among long-distance athletes. Although body awareness is important for injury prevention, the interplay between awareness, behavioral changes, and functional outcomes has not been fully examined.